2015
DOI: 10.4172/2157-7099.1000392
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Neoplasms in Female Dogs: Identification of Cytopathological Criteria for Malignancy

Abstract: Mammary neoplasms have high incidence in both women and female dogs, with such a cytological resemblance between species that studies in canines might work as a baseline for research regarding the incidence in women, due to the relatively high incidence of this cancer, similar biologic behavior, large body size, comparable responses to cytotoxic agents, and shorter overall lifespan. Given the relevance of this neoplasm and the practicality of the cytological examination, studies listing the classification crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…As of malignant tumors, Kamiguchi et al (2016) found the papilliferous carcinoma histological type in 90% of the samples. Gundim et al (2016) found tubular carcinoma, followed by carcinoma in a mixed tumor.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…As of malignant tumors, Kamiguchi et al (2016) found the papilliferous carcinoma histological type in 90% of the samples. Gundim et al (2016) found tubular carcinoma, followed by carcinoma in a mixed tumor.…”
Section: Discussionmentioning
confidence: 95%
“…Feliciano et al (2012) evaluated 60 female dogs, of which 13.37% had received contraceptives. Kamiguchi et al (2016), when conducting the study with 20 female dogs, noted that 10% of the patients had a history of hormone administration for contraceptive purposes, which could indicate a low correlation with the development of mammary tumors. Ariyarathna et al (2018) studied 74 female dogs and none of them had used contraceptives to prevent pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations